2016
DOI: 10.4067/s0717-66432016000100002
|View full text |Cite
|
Sign up to set email alerts
|

Variación en atributos anatómicos asociados a la conducción y almacenamiento de agua, en tres poblaciones de Maihuenia poeppigii (Otto ex Pfeiff.) K. Schum. (Cactaceae) en un gradiente altitudinal

Abstract: Variación en atributos anatómicos asociados a la conducción y almacenamiento de agua, en tres poblaciones de RESUMENLa variabilidad en atributos anatómicos de las plantas podría estar relacionada con las condiciones del medio donde ellas se desarrollan (bajas temperaturas, estrés hídrico, corta estación de crecimiento), y esta variabilidad refl ejaría la capacidad de una especie de establecerse en hábitats que difi eren en la disponibilidad de estas condiciones. Maihuenia poeppigii (Otto ex Pfeiff.) K. Schum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…The reduction of hydraulic efficiency may be related to the limitation in d , d h and D a (Table S1). Mean tracheid diameter decreased while VD increased with increasing elevation, which is consistent with previous studies (Hernandez‐Fuentes et al, 2015) and supports the hypothesis that trees growing in high elevations subjected to frost drought have smaller tracheid diameters than the same species in warmer areas at lower elevations (Cabral et al, 2016). When temperatures drop in October and frost drought can occur at higher elevations in winter (Charrier et al, 2017; Earles et al, 2018), embolism formation can be induced.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The reduction of hydraulic efficiency may be related to the limitation in d , d h and D a (Table S1). Mean tracheid diameter decreased while VD increased with increasing elevation, which is consistent with previous studies (Hernandez‐Fuentes et al, 2015) and supports the hypothesis that trees growing in high elevations subjected to frost drought have smaller tracheid diameters than the same species in warmer areas at lower elevations (Cabral et al, 2016). When temperatures drop in October and frost drought can occur at higher elevations in winter (Charrier et al, 2017; Earles et al, 2018), embolism formation can be induced.…”
Section: Discussionsupporting
confidence: 90%
“…Narrower vessels can reduce the risk of embolization to some extent, although they sacrifice part of the water transport efficiency (Christensen‐Dalsgaard & Tyree, 2014; Dai et al, 2020). Therefore, numerous studies found that vessels in plants at high elevations tended to be smaller to strengthen the embolism resistance in the xylem, revealing the adaptive strategies of plants to maintain the necessary water availability for growth and to cope with environmental stress (Cabral et al, 2016; Dai et al, 2020; Fisher et al, 2007). However, Maherali et al (2004), who identified the relationship between hydraulic conductivity, embolism resistance and climate in 167 species, found only a weak trade‐off between hydraulic efficiency and embolism resistance.…”
Section: Introductionmentioning
confidence: 99%